Cybercrime in progress: theory and prevention of technology-enabled offenses - Holt, Thomas J. (Crime science series, 2016)
Technology and cybercrime -- Issues in empirical assessments of cybercrime -- Applications of criminological theory to cybercrimes -- Issues in domestic and transnational cybercrime investigation -- Issues in the prevention of cybercrime -- The future of cybercrime and digital forensic research